Pest detection system using machine learning techniques - Prithvi, Protyusha Barua; Zahin, Fabliha; Anny, Sanjida Sultana (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022